Caracterização funcional e estrutural de uma ?-glucanase GH12 de Aspergillus terreus - Dias, Bruno Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The enzymatic conversion of polysaccharides from biomass is a key factor in the development of second generation bioethanol. The recalcitrance of lignocellulose to enzymatic degradation and the high cost of hydrolytic enzymes necessary for the depolymerization of polysaccharides found in plant cell wall are significant barriers to large-scale production and commercialization of biofuels and bioproducts derived from plant biomass. In order to rapidly increase the production of biofuel and byproducts cellulosic, a need exists to develop more efficient and lower cost enzymatic cocktails for the conversion of biomass into fermentable sugars. In this context, the study of cell wall degrading enzymes is essential. In this work the enzyme endo-1,4-?-D-glucanase from Aspergillus terreus (ATEG_09894) was cloned for expression in A. nidulans. The expression test showed the expression of a soluble protein. Its identity was confirmed by mass spectrometry. The optimum pH and optimum temperature for the enzyme activity were 5.0 and 55 ºC, respectively. The thermal denaturation showed that above 60 ºC the enzyme starts to lose structure. Interestingly, the enzyme has ?-glucanase and xiloglucanase activities, preferring ?-glucan. Structural characterization showed that ATEG_09894 was expressed correctly folded and the results of SEC and SAXS show that the protein is monomeric in solution and the model of its three dimensional structure indicates that the electrostatic surface molecule contributes to a stable monomer. The data presented in this study are important because they identify peculiarities of ATEG_09894, which acts in the degradation of biomass, suggest the determinants of its selectivity and enzymatic degradation presents, unusual, of ?-glucans and xyloglucans, promising feature for degradation of lignocellulosic material

A conversão enzimática dos polissacarídeos da biomassa é um fator chave no desenvolvimento de bioetanol de segunda geração. A recalcitrância da lignocelulose para a degradação enzimática e o custo elevado de enzimas hidrolíticas necessárias para a despolimerização de polissacarídeos encontrados na parede celular da planta são barreiras significativas para a produção em larga escala e para a comercialização de biocombustíveis e bioprodutos derivados da biomassa vegetal. A fim de aumentar rapidamente a produção de biocombustíveis celulósicos e bioprodutos, existe a necessidade de desenvolver coquetéis enzimáticos mais eficientes e de menor custo para a conversão de biomassa em açúcares fermentáveis. Nesse contexto, o estudo de enzimas degradadoras da parede celular é essencial. No presente trabalho a enzima endo-1,4-?-D-glucanase de Aspergillus terreus (ATEG_09894) foi clonada para expressão em A. nidulans. O teste de expressão mostrou a expressão solúvel da proteína. Sua identidade foi confirmada por espectrometria de massas. O pH ótimo e a temperatura ótima para sua atividade enzimática foram de 5,0 e 55ºC, respectivamente. A desnaturação térmica mostrou que a partir de 60ºC a enzima começa a perder estrutura. Interessantemente a enzima apresenta atividades ?-glucanase e xiloglucanase, tendo preferência por ?-glucano. A caracterização estrutural mostrou que ATEG_09894 foi expressa corretamente e os resultados de SEC e SAXS mostram que a proteína é monomérica em solução e o modelo de sua estrutura tridimensional indica que a superfície eletrostática da molécula contribui para um monômero estável. Os dados apresentados nesse trabalho são importantes pois identificam peculiaridades da enzima ATEG_09894, que atua na degradação da biomassa, sugerem os determinantes de sua seletividade enzimática e apresenta a degradação, não usual, de ?-glucanos...
Keywords: Microbiologia; Enzimas - Aplicações industriais; Celulase; Aspergillus terreus; Biocombustíveis; Enzymes - Industrial applications